Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Nelson R. Hoskins, December 27, 1986 - Hoskins, Nelson R.et al (1986)
Iowa Christmas bird counts of regular and uncommon species found in Ottumwa contributed by Nelson R. Hoskins, December 27, 1986. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1986-1987. Epson - sheet feed